PROFIL ANAK JALANAN DI KOTA PEKANBARU - Ibrahim, Bedriati (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2015)
This study aims to find, analyze and describe the characteristics of street children,child driving factors become street children, and crimes of street children. This type of researchis descriptive penelitinan. The data used to complete this study consists of the data Primary andSecondary Data. Primary data were obtained berdaserkan field research using the StructuredInterview list has been prepared. while secondary data obtained from the relevant institutionsand library materials related to the presence of street children in the city of Pekanbaru. Thetechnique of data pengmbilan is by observation, structured interviews and documentation. Thedata is then processed ririskiky percent described it descriptive.Based on the findings of theresearch field is 1.) Characteristics of street children in the city of Pekanbaru which include sexmen aged 14-16 years, a job selling newspapers, state schools generally do not go back toschool, junior high school level, area of origin of street children is in the province of Riau, hoursof work 4-6 hours per day, capital comes from an agent, revenue Rp10,000 to Rp20,000, usabilitypendapaan to eat, ideals ciata want the driver, hope street children want to go back to school,where living with parents, long become street children 3-4 years 2.) factors driving childrenstreets become street children, who told them to work is their own will and reason to workbecause of economic pressures. 3.) criminal acts of street children include forms of criminal actsare stealing and pickpocketing, the reason of criminal activity because it requires money, victimsof criminal acts asyarakat around, many street children who have experienced violence, violenceis a form of physical violence, abusers thugs, an effort to avoid violence by allowing only whatis experienced, there are street children who had sexual intercourse, sexual intercourse withprostitutes, sexual intercourse is the reason of their own accord, street children into the community,never experienced acts of violence from other communities in the form of physical violence,street children many motorcycle accident, street children ever done hanyab raided and records,street children are not satisfied with the governmentâs treatment of the desired concrete form ofgovernment is skills training and daily needs.Keywords: Profile, Street Children, Pekanbaru